1985
DOI: 10.1002/ijc.2910350209
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of 5‐azacytidine, phorbol ester, and retinoic acid on the malignant phenotype of human lung cancer cells

Abstract: Cloned human cell lines of squamous-cell lung carcinoma and small-cell lung carcinoma were treated with 5-azacytidine (5-azaC), 12-0-tetradecanoyl-phorbol-13 acetate (TPA), retinoic acid (RA), or a combination of these drugs, and the effects on cellular morphology, in vitro growth properties, antigenicity, tumorigenicity and metastatic activity in nude mice were studied. Antigenicity was measured by the expression of major histocompatibility antigens (MHC) and of lung-tumor-associated antigens. 5-AzaC treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The lack of correlation between DNA methylation levels and malignant phenotype has been observed by others [31,32]. Several of these clones also exhibited decreased DNA methylation levels, but the correlation was hOt absolute.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The lack of correlation between DNA methylation levels and malignant phenotype has been observed by others [31,32]. Several of these clones also exhibited decreased DNA methylation levels, but the correlation was hOt absolute.…”
Section: Discussionsupporting
confidence: 51%
“…Recent evidence indicates that eukaryotic gene expression is controlled, at least in part, by DNA methylation at specific cytosine residues [4,36,37]. We, and others, have begun to test this hypothesis by experimental manipulation of DNA methylation levels in well-characterized tumor cell populations by treatment with DNA hypomethylating agents and examining subsequent shifts in their malignant properties [20,25,[30][31][32][39][40][41]. We, and others, have begun to test this hypothesis by experimental manipulation of DNA methylation levels in well-characterized tumor cell populations by treatment with DNA hypomethylating agents and examining subsequent shifts in their malignant properties [20,25,[30][31][32][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, inhibition has been attributed to cytostasis rather than cytotoxicity since viability is maintained and growth arrest is reversible (Jeten, 1984). When cellular kinetic analyses have been performed, increases in the duration of S-phase have been reported for 3T3 fibroblasts and several breast carcinoma lines (Schroder et al, 1982;Marth et al, 1985), while GI blocks have been shown for Chinese hamster ovary cells, murine melanoma, human HeLa and several lung carcinoma lines (Haddox and Russell, 1979;Lotan et al, 1981;Dion and Gifford, 1980;Marth et al, 1985;Olsson et al, 1985). When [3H]-thymidine incorporation has been examined, decreased incorporation has correlated with growth inhibition (Haddox and Russel, 1979;Ueda et al, 1980;Schroder et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, natural retinoids have been used in the treatment of lung cancers since the late 70's when the first human trials were conducted [4], [5], [6], [7] on the basis of antiproliferative effects specific to epithelial tissues and tumors [8], [9], [10], [11]. The development of synthetic retinoids occurred subsequently in an attempt to retain vitamin A's antiproliferative effects specific to epithelial tissue while avoiding dose limiting side effects such as skin and liver toxicity [4], [12].…”
Section: Introductionmentioning
confidence: 99%